An Online Ethics Curriculum for Short-Term Global Health Experiences: Evaluating a Decade of Use - Chelsea E. Modlin; Matthew DeCamp; Michele Barry; Danica Rockney; Jeremy Sugarman (Ubiquity Press, 2022)
Background: Medical students and early career healthcare professionals commonly participate in short-term experiences in global health (STEGH). Objective: The authors evaluate the use of a free-to-access, case-based online curriculum addressing ethical issues trainees should consider prior to engaging in STEGH. Methods: Demographic data and feedback on specific cases were collected from 5,226 respondents accessing the online curriculum between November 1, 2011 and October 31, 2021. Feedback on the curriculum included 5-point Likert scale and open-ended responses. Quantitative data were analyzed using standard descriptive statistics. Qualitative data were independently dual coded and analyzed thematically in NVivo. Findings: The curriculum reached respondents from 106 countries. Undergraduate (36%) and graduate (38%) respondents included those from several different professional specialties. Less than a quarter of all of respondents, less than half with previous global health experience, and one-third with planned future global health experiences had received prior global health ethics training. Overall, the curriculum was highly rated; respondents felt it provided necessary tools to improve their thought processes, confidence, and behavior when encountering ethical issues during STEGH. Areas for curriculum improvement include balancing case specificity with generalizability. Conclusion: This curriculum has met a need for accessible introductory global health ethics education and demonstrates successful use of an online platform in case-based ethics learning.